Health assessment for nursing practice - Wilson, Susan Fickertt (Mosby, 2013)
Using a nursing-oriented, holistic approach, this straightforward text provides you with a visual presentation to conducting physical examinations. This textbook clearly delineates the routine exam techniques from those exams for special circumstances or advanced practice.